Unconventional Charge–Spin Conversion in Weyl‐Semimetal WTe2. Issue 38 (9th August 2020) - Zhao, Bing; Karpiak, Bogdan; Khokhriakov, Dmitrii; Johansson, Annika; Hoque, Anamul Md.; Xu, Xiaoguang; Jiang, Yong; Mertig, Ingrid; Dash, Saroj P.
Abstract: An outstanding feature of topological quantum materials is their novel spin topology in the electronic band structures with an expected large charge‐to‐spin conversion efficiency. Here, a charge‐current‐induced spin polarization in the type‐II Weyl semimetal candidate WTe2 and efficient spin injection and detection in a graphene channel up to room temperature are reported. Contrary to the conventional spin Hall and Rashba–Edelstein effects, the measurements indicate an unconventional charge‐to‐spin conversion in WTe2, which is primarily forbidden by the crystal symmetry of the system. Such a large spin polarization can be possible in WTe2 due to a reduced crystal symmetry combined with its large spin Berry curvature, spin–orbit interaction with a novel spin‐texture of the Fermi states. A robust and practical method is demonstrated for electrical creation and detection of such a spin polarization using both charge‐to‐spin conversion and its inverse phenomenon and utilized it for efficient spin injection and detection in the graphene channel up to room temperature. These findings open opportunities for utilizing topological Weyl materials as nonmagnetic spin sources in all‐electrical van der Waals spintronic circuits and for low‐power and high‐performance nonvolatile spintronic technologies. Abstract : An outstanding feature of the topological Weyl semimetal WTe2 is its novel spin topologies in the electronic band structure. An unconventional charge–spin conversion in WTe2 due to its lower crystal symmetry combined with large Berry curvature and spin‐texture of the Fermi states is demonstrated. These findings have great potential for utilizing WTe2 for spintronic circuits and quantum technologies.